2006
DOI: 10.1080/10245330600702893
|View full text |Cite
|
Sign up to set email alerts
|

t(8;21) (q22;q22) Acute myelogenous leukemia in México: A single institution experience

Abstract: We analyze the prevalence and clinical features of a group of patients with t(8;21) (q22;q22) acute myeloblastic leukemia, identified in a single institution in México over a 10-year period. Fifteen patients presented at the Centro de Hematología y Medicina Interna de Puebla from February 1995 to August 2005; only nine were treated and followed in the institution. Median age was 24 years, (range 7-49); there was only one male. According to the French-American-British (FAB) morphological classification of leuke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…Additionally, the presence of translocation t(8;21)(q22;q22) is associated with a relatively good prognosis when treated with standard daunorubicin and cytarabine induction therapy, followed by high-dose cytarabine [8]. The association with t(8;21)(q22;q22) has also demonstrated no adverse prognostic factor in the AML patients even with GS [4]; however, other reports suggest the opposite results [17]. Two patients in our series had an association with t(8;21) and had a better survival outcome.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, the presence of translocation t(8;21)(q22;q22) is associated with a relatively good prognosis when treated with standard daunorubicin and cytarabine induction therapy, followed by high-dose cytarabine [8]. The association with t(8;21)(q22;q22) has also demonstrated no adverse prognostic factor in the AML patients even with GS [4]; however, other reports suggest the opposite results [17]. Two patients in our series had an association with t(8;21) and had a better survival outcome.…”
Section: Discussionmentioning
confidence: 99%
“…AML, characterized by the aberrant proliferation of myeloid stem cells, reduced apoptosis and blockage in cellular differentiation, is usually associated with a complex translocation, e.g. t(8;21)(q22;q22) with other complex variants and the transcription factor fusion protein, RUNX1-RUNX1T1 (also known as AML1-ETO) [2,3,4]. GS has been reported to be associated with t(8;21) translocation and can present either before, concurrent with or after the onset of AML.…”
Section: Introductionmentioning
confidence: 99%
“…Although the presence of translocation t(8;21) is associated with a relatively good prognosis when treated with standard induction and intensive consolidation chemotherapy, it remains unclear whether this favorable prognosis remains in the presence of EM disease because there are conflicting reports. 73, 74 Byrd et al analyzed 84 AML patients with t(8;21) and reported that those with EM disease had significantly worse survival, which in 74 In a later study of 20 patients with isolated MS by Tsimberidou et al, the presence of cytogenetic abnormalities, specifically abnormalities in chromosome 8, appeared to confer a worse outcome, although this was not statistically significant. 72 However, a more recent study by the same authors helped clarify this issue to some degree by comparing outcomes in 16 patients with isolated MS with those of a large cohort of AML who underwent standard treatment.…”
Section: Does the Presence Of Em Involvement Confer A Worse Prognosismentioning
confidence: 99%
“…Although the presence of translocation t(8;21) is associated with a relatively good prognosis when treated with standard induction and intensive consolidation chemotherapy, it remains unclear whether this favorable prognosis remains in the presence of EM disease because there are conflicting reports. 73,74 Byrd et al analyzed 84 AML patients with t(8;21) and reported that those with EM disease had significantly worse survival, which in For personal use only. on May 11, 2018. by guest www.bloodjournal.org From part could have been the result of including a high proportion of patients with spinal or meningeal involvement.…”
Section: Does the Presence Of Em Involvement Confer A Worse Prognosismentioning
confidence: 99%
“…13 In Mexico, novel treatments for AML such as gemtuzumab-ozogamicin have been restricted due to their high costs. The introduction of BMT with reducedintensity conditioning on an outpatient basis is associated with favorable AML outcomes.…”
Section: Acute Myeloid Leukemia (Aml)mentioning
confidence: 99%